Assessment of soil fertility status in different isolated land use types - Abdul Malik, Mohammad Nazrin (2015)
Information on soil properties in different land uses is vital for the understanding of ecological information as a useful tool and guideline for further management and practices for soil management, since plants can absorb and utilize only a portion of the total nutrient content in soil. However,many doubts remain concerning the method of evaluating the success of human activities in restoring degraded land for sustaining soil fertility and productivity. Most of the available soil indices worldwide apply only to temperate soil. Hence, there is a need for suitable indices to quantify the quality of degraded land in the tropics. Soil Fertility Index and Soil Evaluation Factor as a tool in determining soil fertility status among the sites (forest plantation, oil palm plantation, secondary forest and pasture area) could provide crucial information regarding the current status of the soils and interpreted soil condition as a basic factor for recommending fertilizer application and soil management. This study is divided into three chapters, corresponding to the following objectives: (1) to characterize the soil properties in five different land uses (forest plantation, Pinus caribaea and Swietenia macrophylla; secondary forest (SISFEC); oil palm plantation; and pasture area); (2) to determine soil fertility status using soil fertility index (SFI) and soil evaluation factor (SEF) of three different sites: Pinus caribaea plantation, Swietenia macrophylla plantation, and pasture area, including the analysis of the growth performance between Pinus caribaea and Swietenia macrophylla planted in the rehabilitated degraded land; and (3) to assess the soil fertility status using SFI and SEF of two different lands uses, secondary forest and oil palm plantation. This study was conducted under forest plantation (Pinus caribaea and Swietenia macrophylla), secondary forest (SISFEC), oil palm plantation, and pasture area at Universiti Putra Malaysia's Serdang Campus in Selangor, Malaysia. To address the first objective, soil profiles were dug up to 100 cm depth and 50 cm width. Next, the soil was sampled according to soil horizons, and soil morphology was determined using field technique. To address the second objective, composite samples were collected within the six study plots (20x20m) at Pinus caribaea plantation, Swietenia macrophylla plantation and pasture area at depths of 0-20 cm (surface soil) and 20-40 cm (subsurface soil). For the third objective, soils were sampled at depths of 0-20 cm (surface soil) and 20- 40 cm (subsurface soil) in six plots (20x20 m) in the secondary forest and oil palm plantation plot. The samples were air-dried, homogenized and sieved to pass a 2-mm mesh sieve for further analysis. Laboratory analyses included physico-chemical properties, sesquioxides content, charge characteristic, and mineralogical properties. Soil fertility status was evaluated using two indices,Soil Fertility Index and Soil Evaluation Factor. Data were analyzed using Statistical Package Social Science (SPSS) version 20. Results obtained for the first objective found A horizon in all of the soil profiles. The soil color for all profiles ranged from reddish brown to dark brown (surface), which resulted from the decomposition of organic matter. The soils of all profiles were acidic, ranging from 3.6 to 5.2 in their acidity, with acidity levels increasing with depth. Cation exchange capacity and total carbon tended to decrease with depth, and higher in the secondary forest and pine plantation than in mahogany plantation, oil palm plantation and pasture area. Exchangeable K, Ca and Mg were higher in the topsoil than in the subsoil for most profiles. Exchangeable Al increased with depth and available P in the soil ranged from 0.72 to 1.98 mg/kg. The Alo, Ald, Feo and Fed increased with depth in all profiles. The clay mineral composition was dominated by 1:1 type kaolin minerals. The point zero of salt effect values tended to increase, while the σp values decreased with depth at all sites, indicating that the soils are highly weathered. The assessment for the second objective found no significant differences (p<0.05) in the bulk density of the soils in the Pinus caribaea and pasture plots. In contrast, the topsoil of Swietenia macrophylla plots possessed lower bulk density (p<0.05) compared to the other plots. The pasture plot had higher (p<0.05) moisture content compared to that of Swietenia macrophylla and Pinus caribaea plots for both soil depths. The soils at the three experimental sites were slightly acidic, with pH ranging from 4.12 to 5.09 in the topsoil and 4.27 to 4.92 in the subsoil. Organic matter was found to be significantly higher (p<0.05) in the pasture than in Swietenia macrophylla and Pinus caribaea plots. Pinus caribaea plots showed significantly higher (p<0.05) level of total carbon at both soil depths compared to the other study plots. Exchangeable Ca, Mg and K were significantly higher (p<0.05) in the topsoil of Pinus caribaea compared to the other plots. Cation exchange capacity and effective cation exchange capacity of the soils were low. PCA results indicated that soil texture,OM, TC, TN, nutrient content and cation exchange capacity had a strong positive relationship, which explains the higher SFI value in the nutrients in the soil especially the topsoil in Pinus caribaea than the other study plots. In contrast, pasture plot had higher SEF, followed by Pinus caribaea and Swietenia macrophylla plantation plots. The results for the third objective showed that clay composition was the highest in the oil palm plantation for both surface and subsurface soil. The pH value in surface and subsurface soil for oil palm plantation is higher than in secondary forest. Soil in oil palm plantation exhibited higher organic matter content compared to secondary forest. The total carbon and nitrogen were higher in the oil palm plantation at surface soil. The cation exchange capacity was highest in the oil palm plantation for both surface and subsurface soils. The exchangeable Ca, Mg, K were higher in the oil palm plantation for surface and subsurface soil. Exchangeable Al for surface soil was also higher in the oil palm plantation. The value of Soil Fertility Index was higher than Soil Evaluation Factor value for both depths in the oil palm plantation compared to secondary forest. In conclusion, all of the soils (forest plantation, Pinus caribaea and Swietenia macrophylla; secondary forest (SISFEC); oil palm plantation; and pasture area) were very acidic, highly weathered and considered poor in soil nutrient content,which exhibited Ultisols and Oxisols characteristic. The physico-chemical properties were the main factor that contributed to nutrient resources and soil fertility. The soil fertility status of the Pinus caribaea plantation was superior to that of the Swietenia macrophylla plantation and pasture area, which indicated that forest plantation is a proper technique for rehabilitating and replenishing soil fertility of degraded land. Soil fertility was affected by the types of crops or trees that grow in the soil, as their characteristics affect their nutrient uptake. The oil palm plantation soil showed the highest Soil Fertility Index value compared to secondary forests. Moreover, soil fertility was affected by different types of soil management, parent materials, and climatic conditions.